Open reflections on virtual meetings on the Internet - Grau, Jordi (Anuario ThinkEPI, 2008)
Videoconferences, collaboration tools, or virtual meeting software have all been in use for years on the Internet and have steadily become more affordable and accessible. Nevertheless, their actual presence in organizations is still very small: technological and cultural problems remain before these tools can achieve the broad public use that could lower the price of communications and save the costs associated with travel to meetings.
Keywords: Videoconference; Webconference; Virtual meetings; Collaboration; Remote attendance; Remote access.